Structural stability of Sclerotium rolfsii ATCC 201126 β-glucan with fermentation time: a chemical, infrared spectroscopic and enzymatic approach - Fariña, Julia Ines (2009)
Sclerotium rolfsii ATCC 201126 exopolysaccharides (EPSs) recovered at 48 h (EPS I) and 72 h (EPS II) of fermentation, with differences in rheological parameters, hydrogel topography, salt tolerance, antisyneresis, emulsifying and suspending properties, were subjected to a polyphasic characterization in order to detect structural divergences. Methods and Results: Fermenter-scale production led to productivity (Pr) and yield (YP ⁄ C) values higher at 48 h (Pr = 0Æ542 g l)1 h)1 ; YP ⁄ C = 0Æ74) than at 72 h (Pr = 0Æ336 g l)1 h)1 ; YP ⁄ C = 0Æ50). Both EPSs were neutral glucosehomopolysaccharides with a b-(1,3)-glycosidic backbone and single b-(1,6)- glucopyranosyl sidechains regularly attached every three residues in the main chain, as revealed by chemical analyses. The infra-red diagnostic peak at 890 cm)1 confirmed b-glycosidic linkages, while gentiobiose released by b-(1,3)-glucanases confirmed single b-1,6-glycosidic branching for both EPSs. Conclusions: The true modular repeating unit of S. rolfsii ATCC 201126 scleroglucan could be resolved. Structural stability was corroborated and no structural differences could be detected as to account for the variations in EPSs behaviour. Significance and Impact of the Study: Recovery of S. rolfsii ATCC 201126 scleroglucan at 48 h might be considered based on better fermentation kinetic parameters and no detrimental effects on EPS structural features.